1966
DOI: 10.1126/science.152.3718.25
|View full text |Cite
|
Sign up to set email alerts
|

Inductive Processes in Embryonic Development

Abstract: observed ionospheric peak might be an Fl region produced by solar ultraviolet radiation. It is still plausible in this case that no F2 peak will develop, and the thermal structure is not likely to differ importantly from that shown in Fig. 2 (18). A more thorough analysis of the spectroscopic data is given by M. J. S. Belton and D. M. Hunten (Astrophys. J., in press). The spectroscopic technique is discussed in a review by J. W. Chamberlain and D. M. Hunten [Rev. Geophys. 3, 299 (1965)]. 3. M. B. McElroy, J. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
1
1

Year Published

1967
1967
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(115 citation statements)
references
References 15 publications
7
106
1
1
Order By: Relevance
“…One could call these early effects on the future ectodermal regions either an initial induction or a change in competence. This situation is similar to the finding that the "changing competence" of the prospective lens ectoderm is due to early induction events (Jacobson, 1966). In any event, the ventral and dorsal inductive signals could cause each of the two ectodermal regions to embark on a process of progressive determination, early stages of which may be labile or reversible.…”
Section: Discussionsupporting
confidence: 79%
“…One could call these early effects on the future ectodermal regions either an initial induction or a change in competence. This situation is similar to the finding that the "changing competence" of the prospective lens ectoderm is due to early induction events (Jacobson, 1966). In any event, the ventral and dorsal inductive signals could cause each of the two ectodermal regions to embark on a process of progressive determination, early stages of which may be labile or reversible.…”
Section: Discussionsupporting
confidence: 79%
“…Both the hindbrain and mesendoderm have been implicated as signaling sources for otic placode induction (Waddington, 1937;Jacobson, 1966;Chisaka et al, 1992;Moens et al, 1998;Woo and Fraser, 1998;Mendonsa and Riley, 1999), and various FGF signals are expressed in one or both of these tissues in chick, Xenopus, zebrafish, and mouse during otic placode development (Wilkinson et al, 1988(Wilkinson et al, , 1989Niswander and Martin, 1992;Tannahill et al, 1992;Mahmood et al, 1995;McKay et al, 1996;Ladher et al, 2000;Phillips et al, 2001). A role for mesendodermal FGF signaling is seen in chick, in which FGF19-expressing mesoderm can induce Wnt8c expression in adjacent neural tissue, and together these induce expression of otic markers and placode-like structures in tissue culture (Ladher et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Similar experiments using chick embryos demonstrated that limb-type identity is determined by the origin of the graft (Hamburger, 1938): tissue taken from the wing-forming region produces an ectopic wing and cells transplanted from the leg-forming region always produce a new leg. Tissue grafts from the prospective limb-forming tissue therefore behave as classically defined developmental fields in that they have the properties of self-determination and selforganisation (Jacobson and Sater, 1988). Building upon these original observations, more extensive transplantation experiments in the chick have mapped the temporal and spatial sequence of the limb-forming capacity of the LPM (Stephens et al, 1989).…”
Section: Lessons From Classical Embryological Studiesmentioning
confidence: 99%